P34 Sarcoidosis and co-existent Aspergillus lung disease. (12th November 2015) - Gudur, S; Nuttall, E; Harris, C; Chaudhuri, N; Leonard, C; Muldoon, E
Abstract : Sarcoidosis is a multisystem disorder which affects the lungs and in a small percentage of cases may result in fibrosis and cystic cavitating lesions. Chronic pulmonary aspergillosis (CPA) typically affects patients with underlying lung conditions; immunosuppressive therapy is not recommended due to risk of progression or spread of Aspergillus infection. Sarcoid patients are often significantly debilitated when they develop co-existent Aspergillus lung disease. They can present with worsening breathlessness, weight loss and significant haemoptysis. There is no consensus on how to best treat patients diagnosed with Sarcoid and CPA. Methods: A retrospective review of patients diagnosed with Sarcoidosis and CPA was performed. Cases were identified from a database held of patients diagnosed with CPA group in our specialist clinic. Patient demographics, presentation, laboratory parameters, radiology results were recorded and data analysed. Results: 38 patients with sarcoidosis were diagnosed with CPA from 2009 – March 2015. 23/36 (63%) were male. 14/36 (38%) patients were affected by breathlessness with MRC dyspnoea score ≥3. 15/36 (41%) of patients were on maintenance Prednisolone between 5 – 10 mg/day and 3 patients on other steroid sparing agents. 12/28 patients had obstructive spirometry and average predicted gas transfer factor at 49% (range 20 – 75%). 33/36 (91%) had CPA defined by presence of serum precipitins and 50% of patients had aspergillomas detected in the cavities on radiology. 27/36 (75%) of patients were on antifungal therapy. On regular follow-up, antifungal therapy was titrated based on serum azole levels and as tolerated. 4/36 (11%) patients had been treated for proven TB and 2/36 were on empirical treatment until TB diagnosis was excluded when there was clinical and radiological deterioration. Conclusions: Although sarcoidosis has slight female predominance, in this cohort of patients with CPA and sarcoid 63% were males. Many of the patients had significant lung disease with high MRC dyspnoea scores, and obstructive spriometry often with low gas transfers. The management of CPA in the setting of sarcoidosis is complex due to the risk of immunosuppression and interactions with antifungal therapy. Close working between specialties is important in optimising such patients, to ensure the best patient outcomes.